Roughing up beta: Continuous versus discontinuous betas and the cross section of expected stock returns - Bollerslev, Tim; Li, Sophia Zhengzi; Todorov, Viktor (Journal of Financial Economics, 2016)
We investigate how individual equity prices respond to continuous and jumpy market price moves and how these different market price risks, or betas, are priced in the cross section of expected stock returns. Based on a novel high-frequency data set of almost 1,000 stocks over two decades, we find that the two rough betas associated with intraday discontinuous and overnight returns entail significant risk premiums, while the intraday continuous beta does not. These higher risk premiums for the discontinuous and overnight market betas remain significant after controlling for a long list of other firm characteristics and explanatory variables.